Comparison between the performance of spectrogram and multi-window spectrogram in digital modulated communication signals - Tan Jo, Lynn; Sha'ameri, Ahmad Zuri (2007)
In this paper,we compare the performance of spectrogram and new variation of multi-windows(WM)spectrogram for various digital modulated signals.The windows used in the MW spectrogram are conbination of Slepian sequences instead of using all the sequences.The comparison in the time-frequency representation is made in terms of main-lobe width(WLM)and peak to side-lobe ratio(PSLR)of the signals used.In the presence of noise,performance is compared in terms of variance in the estimated from the instantaneous frequency.Bit duration and frequency are estimated from the time-frequency the instantaneous frequency(IF),which is derived from the time-frequency representation.The bias in the estimated bit duration is also calculated to compare the performance between spectrogram and WM spectrogram. In general,the time-frequency representation for the spectrogram is better than WM spectrogram.However,WM spectrogram is superior to spectrogram in terms of bit duration estimation.